Suffering Related to Care - Rusová Jitka, /; Hlaváčková, Eva (University of Pardubice, 2017)
Introduction: The meaning and objective of caring is to alleviate suffering. In spite of this fact patients sometimes perceive the provided care as a source of suffering. Care that causes suffering has many forms, ranging from all forms of omission or neglecting the patient and ending with (ab)using the caretaker’s power, ultimately resulting in threatening patient’s life and health and violation of his/her human dignity. Objective: The aim of this study is to outline the concept of suffering related to nursing care. Method: A bibliographic survey focused on the phenomenon of suffering related to care. Results: Suffering related to care (uncaring) arises due to healthcare actions that neglect the holistic and patient-centred approach to care. Inspired by D. J. Riemen, S. Halldorsdottir constructed a theory of caring and uncaring encounters in nursing and health care. Conclusion: Suffering related to care exists but is not inevitable. Reflection on this phenomenon can contribute to changes in the healthcare personnel’s behaviour and attitudes.
Keywords: caring; nursing care; suffering; uncaring